Catalytic decomposition of ammonia and tar for hot gas cleanup in biomass gasification using activated carbon supported catalysts and natural limonite ores - Donald, Jaclyn (My University, 2009)
Biomass gasification produces a gas (or syngas) containing primarily CO2, H2, CO, CH4 and (C2+C3), as well as some contaminants such as tars, NH3, H2S and SO2. In order to achieve better efficiencies of the syngas applications, these contaminants must be removed or converted before the syngas is used for internal combustion, gas engines, and in particular for fuel cells and methanol synthesis. Compared with conventional wet scrubbing technologies, catalytic decomposition of ammonia and tar is more advantageous with respect to energy efficiencies.
Keywords: Biomass gasification; Limonite; Ammonia; Catalysis; Tar